Psychological Conflict of a Palestinian Civilian in the Short Story Al-Qamish Al-Masruq by Ghassan Kanafani - Ilmi, Dianatul; Zuhdy, Halimi (Universitas Airlangga, 2025)
The life of Palestinian society in refugee camps is full of economic, social, and moral pressures that influence the way they survive and make decisions. This reality is also reflected in the short story Al-Qamish al-Masruq (The Stolen Shirt) by Ghassan Kanafani through the character of Abu al-Abd. This study aims to (1) identify the dominance of the id, ego, and superego within the character, and (2) analyze the inner conflict through the clash of these three components. The method used is descriptive qualitative with data consisting of the short story text and literature on Freud's psychoanalytic theory. The data were collected using the reading-and-note-taking technique and analyzed through the stages of reduction, presentation, and conclusion drawing. The results of the study indicate that the id triggers impulsive drives, the ego mediates with rational considerations, while the superego demands moral obedience which culminates in an act of violence as a form of resistance against injustice. The conclusion of the study emphasizes that the clash of the id, ego, and superego within Abu al-Abd illustrates not only an internal struggle but also a portrait of the social wounds experienced by Palestinian refugees. This finding is expected to enrich perspectives on psychological crises in Palestinian literary works as a depiction of the collective trauma of its society.